Effect of topically applied silver compounds on the demineralisation of hydroxyapatite. Issue 4 (April 2022) - Huang, W.-T.; Anderson, P.; Duminis, T.; Shahid, S.
Abstract: Objectives: This study investigates the demineralization inhibitory mechanisms of AgNO3, AgF and silver diamine fluoride (SDF) using a previously used hydroxyapatite (HAP) caries demineralization model system. Methods: HAP discs were allocated into three groups (n = 3) and immersed in demineralization solution (buffered pH 4.0, 0.1 mol/L acetic acid) for 4 h. Each disc was treated topically with either 3.16 M AgNO3, 3.16 M AgF or 3.16 M SDF using a micro-brush. The discs were then demineralized for a further 4 h. Calcium, silver, and fluoride ion selective electrodes (ISEs) were used to monitor the changes in each ion concentration at 1 min intervals throughout. Demineralization inhibition was calculated as the percentage reduction in the rate of calcium ion loss from HAP (PRCLHAP ). Characterization of similarly treated HAP powder was carried out with Magic Angle Spinning-Nuclear Magnetic Resonance Results: The mean PRCLHAP for each treatment group was; AgF (72.3 + 4.8%), SDF (69.7 + 5.3%) and AgNO3 (14.9 + 2.7%). Ag3 PO4 was detected in all HAP powders. CaF2 and fluorohydroxyapatite (FHA) were detected only in powders treated with either AgF or SDF. The demineralization inhibitory efficacy of topically applied AgNO3 results from the formation of a Ag3 PO4 barrier. Whereas, the demineralization inhibitory efficacy of topically applied AgF, and SDF, results from the formation of a barrier composed of Ag3 PO4, CaF2, and FHA. Significance: In addition to their anti-microbial properties, clinical topical application of silver compounds for caries preventative treatment is due to their ability to form acid-resistant barriers composed of silver phosphate. When fluoride is present, this barrier also contains CaF2 and FHA, additionally protecting the mineral.